Activity-based protein profiling - Sieber, Stephan A. (Topics in Current Chemistry, 2012)
M. B. Nodwell S. A. Sieber ABPP Methodology: Introduction and Overview J. Krysiak R. Breinbauer Activity-Based Protein Profiling for Natural Product Target Discovery P. P. Geurink L. M. Prely G. A. van der Marel R. Bischoff H. S. Overkleeft Photoaffinity Labeling in Activity-Based Protein Profiling W. P. Heal E. W. Tate Application of Activity-Based Protein Profiling to the Study of Microbial Pathogenesis Y.-G. Kim A. Saghatelian Functional Analysis of Protein Targets by Metabolomic Approaches.